2017
DOI: 10.3390/jfb8010011
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Pharmacokinetic Properties of Hemoglobin-Based Oxygen Carriers

Abstract: Hemoglobin (Hb) is an ideal material for use in the development of an oxygen carrier in view of its innate biological properties. However, the vascular retention of free Hb is too short to permit a full therapeutic effect because Hb is rapidly cleared from the kidney via glomerular filtration or from the liver via the haptogloblin-CD 163 pathway when free Hb is administered in the blood circulation. Attempts have been made to develop alternate acellular and cellular types of Hb based oxygen carriers (HBOCs), i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 112 publications
2
24
0
Order By: Relevance
“…26 Thus, the results of the biodistribution study shown in Figure 5 strongly suggests that BSA-liposomes are scavenged by MPS, especially Kupffer cells, similar to other protein-encapsulated liposome preparations. 27,28 Although we did not investigate the fate of each component of the BSA-liposomes after degradation, they would be expected to be completely cleared from the body or reused in the body because BSA-liposomes are composed of biological materials such as phosphatidylcholine, cholesterol, and albumin (PEG is not a biological material, but it is well known that it is cleared from the body 29 ). Taken together with these evidence, we conclude that BSA-liposomes show good metabolic performance (no accumulation in the body).…”
Section: Discussionmentioning
confidence: 99%
“…26 Thus, the results of the biodistribution study shown in Figure 5 strongly suggests that BSA-liposomes are scavenged by MPS, especially Kupffer cells, similar to other protein-encapsulated liposome preparations. 27,28 Although we did not investigate the fate of each component of the BSA-liposomes after degradation, they would be expected to be completely cleared from the body or reused in the body because BSA-liposomes are composed of biological materials such as phosphatidylcholine, cholesterol, and albumin (PEG is not a biological material, but it is well known that it is cleared from the body 29 ). Taken together with these evidence, we conclude that BSA-liposomes show good metabolic performance (no accumulation in the body).…”
Section: Discussionmentioning
confidence: 99%
“…influence of the size and surrounding shell on the pharmacokinetic properties has helped to decrease side effects (Taguchi et al, 2017). Of note, crosslinking agents and shell material may also cause immunoreactions or increase Met-Hgb formation (Centis and Vermette, 2009).…”
Section: Classes Of Aocsmentioning
confidence: 99%
“…We also previously reported the CO-HbV showed no severe adverse effects including death, and clinical laboratory tests and histopathological changes remained normal for 28 days (Nagao et al., 2016a ). Taken together, the safety profiles of HbV such as its biological compatibility, the absence of toxicity, the absence of accumulation in the body (Sakai, 2017 ; Taguchi et al., 2017a ), CO-HbV possesses the favorable safety characteristics for use as a CO donor and as a contributor to the therapy against inflammatory disorders. However, it has been still remained some limitations in present study.…”
Section: Discussionmentioning
confidence: 99%
“…8000 nm) (Sakai, 2017 ). These RBC-mimetic structures of HbV have a good biocompatibility and relatively long half-life with Hb, even after a massive infusion (Sakai, 2017 ; Taguchi et al., 2017a ). Furthermore, the phospholipid bilayer membrane that consists of a lipid membrane of HbV allows CO to penetrate, and then easily and stably bind to Hb in the form of HbV as well as RBC (Sakai et al., 2008a , b ).…”
Section: Introductionmentioning
confidence: 99%